Penerapan Model Pembelajaran Berbasis Masalah Setting Kooperatif dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Bimbingan Konseling - Alphonsous Adhika Satya Hanggara; Tininggar Tininggar; Susanti Dyastuti; Narwanto Narwanto; Wiyono Wiyono; Mira Ayu Yulaeka (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The aim of this study is to describe the steps, advantages, and disadvantages of applying the Problem-Based Learning Model in a Cooperative Setting to Counseling Guidance learning at MTs Negeri 1 Klaten, MAN Sukoharjo, and MAN 2 Rembang. This research uses a qualitative approach The informants in this study are Counseling Guidance teachers. Data collection techniques include interviews, observations, and documentation. The results of this study are: (1) The steps of the Problem-Based Learning Model in a Cooperative Setting include conveying goals and orienting students to the problem, organizing students into learning groups, guiding individual and group investigations, developing and presenting the final product, reflecting on the problem-solving process, evaluating learning, and providing rewards; (2) The advantages of the Problem-Based Learning Model in a Cooperative Setting are that students develop the ability to solve real-world problems, construct their own knowledge through learning activities, focus on relevant problems (thus avoiding unrelated material), engage in scientific activity through group work, evaluate their own learning progress, communicate scientifically during discussions or presentations, and overcome individual learning difficulties through peer teaching in group work; (3) The disadvantages of the Problem-Based Learning Model in a Cooperative Setting include the fact that not many teachers are capable of guiding students effectively through problem-solving, it often requires significant time and financial resources, and student activities conducted outside of school are difficult for teachers to monitor. The conclusion of this study is that the Problem-Based Learning Model in a Cooperative Setting has proven to be effective in increasing learning motivation.